The heritage of socialist cities (Russia, Germany, Ukraine) - Malko, Anastasia; Kozlova, Lyudmila (project baikal, 2021)
The prefabricated mass housing in microdistricts has been recently demolished due to the technical, social, functional and aesthetic problems. But it constitutes a significant stage in the history of Soviet town-planning and the heritage which potential has not yet been fully realized. The article presents the methods and basic stages of the international scientific and research project focused on the search of the concepts and strategies for sustainable development of the prefabricated mass housing areas in the 1960-1970s, which was funded by the Volkswagen Foundation.
Keywords: microdistricts with prefabricated mass housing; Soviet heritage; stages of the research and design work; methods of the research work